Modernisation of the Russian state’s political elite in the context of peter the great’s transformations - D. A. Filimonov (Вестник университета)
Early eighteenth century was the age of Peter the Great’s transformations, which affected many spheres of life of Russian society, and, in particular, caused the restructuring of the highest political elite. The reforms were, on the one hand, conditioned by the processes of the late seventeenth century, on the other hand, by the specificity of Peter’s absolutism and the long period of warfare. The article analyses the features of Peter’s reforms of the higher political elite. The background to the reforms has been examined, and Peter the Great’s personnel policy, approaches and principles have been analysed. Particular attention has been paid to institutional change, looking at the mechanisms used by Peter the Great in replacing obsolete institutions with new ones. An analysis of the qualitative composition of the elite made it possible to establish a continuity between the political elite of Peter the Great and the aristocracy of the earlier period, with a change in the principles of interaction. The post-reform Russian state is no longer built on the principles of the “servant state”, but on absolutism with a rationalist approach and the principle of “suitability”.